Albania : Financial System Stability Assessment, including Reports on the Observance of Standards and Codes on the following topics; Banking Supervision and Payment Systems. (IMF Staff Country Reports; Country Report, 2005)
This paper discusses key finding of the Financial System Stability Assessment, including Reports on the Observance of Standards and Codes (ROSC) on the Banking Supervision and Payment Systems in Albania. The assessment reveals that the Albanian financial system is not highly vulnerable to immediate macroeconomic or financial sector shocks. However, accelerating credit growth and increased competition arising from the recent privatization of a dominant (savings) bank may put pressure on the banking system. The financial system is also at an early stage of development.